Quantitative assessment of resilience for earthen structures using coupled plasticity-damage model. (1st October 2018) - Motamedi, M.H.; Iranmanesh, A.; Nazari, R.
Highlights: Structural resiliency is revisited as a novel composite term consists of three interrelated capacities (absorptive, adaptive and transformative). The constitutive model is furnished with combined iso-kinematic hardening internal variables accounts for the adaptive capacity of structural resilience. The softening model includes damage-like effects of cohesion degradation and frictional sliding. For transformative capacity the model adopts the enhanced strain finite element method capturing the propagating fracture through the structural components. Abstract: In this work, structural resiliency is revisited as a composite term which consists of three interrelated capacities. A computational platform for quantitatively assessing the disaster-resilience of earthen structures is introduced with the use of a coupled plasticity-damage constitutive model. This numerical framework addresses the collapse resistance, damage sequences, strength residual state as well as resilience metrics. In particular, the plasticity model is furnished with combined isotropic-kinematic hardening internal variables accounting for the adaptive capacity of structural resilience. To simulate the transformative capacity at structural level, the model adopts the enhanced strain finite element method capturing the propagating fracture through the structural elements. Localized failure is detected by a bifurcation analysis. A cohesive based failure criterion is also incorporated to accurately represent the constitutive softening response in the case of progressive failure. Finally, we analyzed the factors that shape the structural resilience of earthen wall in the face of lateral loading. The performance of the structural system is examined for two conditions, namely fully intact structure and pre-damaged state.